Pengaruh Kecerdasan Emosional dan Perilaku belajar siswa terhadap Pemahaman Konsep Matematika - Hikmatulloh Hikmatulloh (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this study were to: 1) determine the effect of emotional intelligence on understanding mathematical concepts, 2) determine the effect of student learning behavior on understanding mathematical concepts, 3) determine the effect of emotional intelligence and student learning behavior simultaneously on understanding mathematical concepts, and 4) find out the relationship between intelligence and student learning behavior on understanding mathematical concepts. Ex post facto and survey approaches were used to carry out descriptive verification. Questionnaires were distributed to students as instruments. The results showed that 1) students' emotional intelligence had an effect on understanding mathematical concepts, and 2) student learning had an effect on understanding mathematical concepts. 3) Emotional intelligence and student learning behavior affect the understanding of mathematical concepts. 4) There is a relationship between emotional intelligence and student learning behavior in understanding mathematical concepts.